Perhitungan Daya Dukung Fondasi Pada Dinding Penahan Tanah Sungai Wai Malua Desa Wakal - Vernandi Tangmau; Glen Boyke Rehatta; Sjafrudin Latar (Universitas Pahlawan Tuanku Tambusai, 2024)
Soil retaining wall (DPT) is a construction building that functions as a slope stabilizer that has the possibility of landslides. One of the areas that often experiences landslides is the central Maluku road in Wahatu hamlet, Wakal village. The factor that causes landslides is due to the increase in volume caused by high rainfall which makes the widening of the river flow which results in landslides that seep to the roadside. The planning made is only based on the instincts and work experience of the contractors and plus the pile foundation used only uses the nani wood pile foundation so that the strength and durability of the wooden pile foundation must be calculated so that we can find out whether the plan is safe or not. The results of this study stated that the carrying capacity per pole = 0.784739 kg with a total carrying capacity, the number of poles 12 pieces x 0, 784739 kg = 9.417 kg / 9.5 tons and the total weight of the beronjong is 97.5 tons. From the calculation results can be concluded the weight of gabions > the total carrying capacity of wooden piles, then from the weight difference is 9.5 tons – 97.5 is 88 tons